The many faces of George Washington : remaking a presidential icon - McClafferty, Carla Killough, 1958- (Carolrhoda Books, 2011)
Veteran children's author McClafferty takes a look at the life of George Washington by chronicling the fascinating process of creating life-sized statues of Washington using the latest modeling techniques.